House on Tongass Avenue, Ketchikan, Alaska, circa 1929-1930 - Unidentified
House in 1930 owned by George Brown (born 1877 in Germany). Immigrated from Germany then married his wife, Mary Brown (born 1895), Ketchikan, AK. They had 3 children in 1940 (Alfred G. Brown, Lucille Brown, Elsie Brown, and Lelia Brown). House still standing on 1730 Tongass Ave Ketchikan, Alaska. Written on photograph: A new house I helped build. Geo. Brown residence PH Coll 1331.15a